SPECIATION OF AQUEOUS NI(II)-CARBOXYLATE AND NI(II)-FULVIC ACID SOLUTIONS: COMBINED ATR-FTIR AND XAFS ANALYSIS - Strathmann T.J.; Myneni S.C.B. (My University, 2004)
Aqueous solutions containing Ni(II) and a series of structurally related carboxylic acids were analyzed using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) and Ni K-edge X-ray absorption fine structure spectroscopy (XAFS). XAFS spectra were also collected for solutions containing Ni2+ and chelating ligands (ethylenediaminetetraacetic acid, nitrilotriacetic acid (NTA)) as well as soil fulvic acid. Limited spectral changes are observed for aqueous Ni(II) complexes with monocarboxylates (formate, acetate) and long-chain polycarboxylates (succinate, tricarballylate), where individual donor groups are separated by multiple bridging methylene groups. These spectral changes indicate weak interactions between Ni(II) and carboxylates, and the trends are similar to some earlier reports for crystalline Ni(II)-acetate solids, for which X-ray crystallography studies have indicated monodentate Ni(II)-carboxylate coordination. Nonetheless, electrostatic or outer-sphere coordination cannot be ruled out for these complexes. However, spectral changes observed for short-chain dicarboxylates (oxalate, malonate) and carboxylates that contain an alcohol donor group adjacent to one of the carboxylate groups (lactate, malate, citrate) demonstrate inner- sphere metal coordination by multiple donor groups. XAFS spectral fits of Ni(II) solutions containing soil fulvic acid are consistent with inner-sphere Ni(II) coordination by one or more carboxylate groups, but spectra are noisy and outer-sphere modes of coordination cannot be ruled out. These molecular studies refine our understanding of the interactions between carboxylates and weakly complexing divalent transition metals, such as Ni(II).